2008
DOI: 10.1002/gcc.20624
|View full text |Cite
|
Sign up to set email alerts
|

ERK5 is a target for gene amplification at 17p11 and promotes cell growth in hepatocellular carcinoma by regulating mitotic entry

Abstract: Using high-density oligonucleotide microarrays, we investigated DNA copy-number aberrations in cell lines derived from hepatocellular carcinomas (HCCs) and detected a novel amplification at 17p11. To identify the target of amplification at 17p11, we defined the extent of the amplicon and examined HCC cell lines for expression of all seven genes in the 750-kb commonly amplified region. Mitogen-activated protein kinase (MAPK) 7, which encodes extracellular-regulated protein kinase (ERK) 5, was overexpressed in c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
78
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(81 citation statements)
references
References 48 publications
2
78
1
Order By: Relevance
“…Moreover, the MAPK7 gene, encoding for ERK5, was found to be amplified in human HCC specimens and cell lines. 9,10 Nonetheless, limited functional information on its possible role in HCC has been reported. Using two wellestablished cellular models, our in vitro data indicate that inhibition of the ERK5 pathway reduces the proliferation of Huh-7 and HepG2 cells, and that ERK5 activity is necessary for progression in the cell cycle.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the MAPK7 gene, encoding for ERK5, was found to be amplified in human HCC specimens and cell lines. 9,10 Nonetheless, limited functional information on its possible role in HCC has been reported. Using two wellestablished cellular models, our in vitro data indicate that inhibition of the ERK5 pathway reduces the proliferation of Huh-7 and HepG2 cells, and that ERK5 activity is necessary for progression in the cell cycle.…”
Section: Discussionmentioning
confidence: 99%
“…Despite remarkable advances already achieved in the diagnosis and treatment of hepatocellular carcinoma, it still has the secondhighest mortality rate [23,[74][75][76]. Most hepatocellular carcinomas develop as a result of chronic liver disease, which, in combination with several other factors, such as inflammation, oxidative stress, and a hypoxic microenvironment, typically occurring in the liver, can have a role in tumour initiation, progression, and metastasis, importantly contributing to poorer prognosis and hampered therapeutics.…”
Section: Hepatocellular Carcinomamentioning
confidence: 99%
“…Zen et al (39) reported that downregulation of MAPK7 by small interfering RNA suppressed the growth of SNU449 cells, which comprise the HCC cell line with the greatest amplification and overexpression of MAPK7. ERK5, which is phosphorylated during the G2/M phases of the cell cycle, may regulate entry into mitosis in SNU449 cells (40).…”
Section: Mir-143 Downregulates the Expression Of Erk5 And C-fosmentioning
confidence: 99%